Cutting edge advertising how to create the world's best print for brands in the 21st century - Aitchison, Jim (Singapore Pearson Education South Asia Pte Ltd, 2004)
"Reprinted ten times in four years and now revised and updated, this classic book is still the definitive step-by-step guide to creating cutting edge print ads. It covers everything from how advertising works, how brand-building methodologies are changing, how to get an idea, and how copy and art should be crafted."--Book jacket.
Unconventional wisdom -- How to find your voice -- The eight greatest lies you will ever be told -- The creative work before the creative work -- How to get an idea -- The five critical choices -- How to craft visuals -- How to craft copy -- The global view -- The cutting edge agenda.
Includes bibliographical references (page 394) and index.
Keywords: Advertising -- Handbooks, manuals, etc